Dynamics of Structure and Meaning in Pantun by Sutan Takdir Alisjabana: Analysis of Literary Criticism - Clarasita Natasya Naibaho; Rosmawaty Harahap (Winaya Inspirasi Nusantara Foundation, 2024)
Sutan Takdir Alisjahbana, an Indonesian literary figure, captivates audiences not only with his beautiful language but also with the deep messages embedded in his pantun, a form of traditional Malay poetry. Pantun by Sutan Takdir Alisjahbana displays themes related to the past and present. In this analysis, we will focus on the dynamics of the structure and meaning contained in Sutan Takdir Alisjahbana's pantun. This analysis employs a literary criticism approach to understand the meaning of the pantun. Using critical literary analysis, this article aims to reveal the dynamic interaction between structure and meaning in Alisjahbana pantun, highlighting its artistry and the potential of pantun as a medium for conveying deep messages.